A THEORETICAL QUANTUM STUDY OF THE ELECTRONIC PROPERTIES OF MENTOXY DICHLORO PHOSPHOROUS (C10H19OPCl2) - Lashgari, Amir; Ghamami, Shahriar; Govindarajan, M.; Salgado-Morán, Guillermo; Montes Romero, Paola; Gerli Candia, Lorena (Journal of the Chilean Chemical Society, 2018)
A theoretical quantum study of the organophosphorus compound with formula C10H19OPCl2 (MEPCL2) was carried out. The results of the calculations show excellent agreement between experimental and computed frequencies evaluated at the B3LYP/6-311++G(d,p) level of theory. A study of the electronic properties, such as excitation energies and wavelengths were performed employing the time-dependent DFT (TD-DFT) method. Global a chemical reactivity of MEPCL2 was analyzed through global reactivity descriptors, while its local reactivity was analyzed by mean maps of the electrostatic potential. Also, the orbital energies values suggest that a charge transfer is occurring within the molecule.